A perspectiva de inovação na administração pública e a gestão de recursos financeiros no âmbito da pós-graduação de uma universidade da região amazônica: estudo de caso da Universidade Federal do Oeste do Pará e a gestão de recurso Centralizado PROAP - CHIBA, Tatiane Mieko de Sousa (Universidade Federal do Oeste do Pará, 2024)
The paper presents a study on Innovation in Public Administration and the relationship with Higher Education in Brazil, using the Federal University of Western Pará (Ufopa) as a reference, and proposes new ways of optimizing the management, monitoring and use of Postgraduate financial resources in this case study. The methodological approach was qualitative, using a bibliographic and documentary base, and the help of qualified informants (coordination and secretariats of postgraduate programs, Postgraduate Directorate, Planning Directorate and Ufopa's Evaluation and Institutional Information Directorate). The theoretical aspect highlights the financial limitations in the financing of Higher Education, directed at Postgraduate Studies in Brazil, in addition to the internal limitations in the application of resources; in the practical aspect, the instrumentalization for the use of resources and, with this, positively impact the use of resources by teachers and students, which will have a positive impact on society. There is little literature that analyzes and discusses innovation in the management of resources in postgraduate studies. In addition, there are obstacles to the advancement of innovation in federal public management in this area, and this becomes more important because over time there have been fluctuations in the financing of public higher education and this has had an impact on postgraduate studies with a reduction in the application of resources. The study therefore proposes a manual and an online information panel using Business Intelligence (BI) systems to monitor the use of resources, to assist postgraduate programs in the use of their financial resources, as an element of management and innovation in the federal public education sector, and public governance.